2018
DOI: 10.1016/j.amepre.2018.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Nutrition Policies and Dietary Intake in Child Care Homes Participating in Healthy Eating and Active Living Initiative

Abstract: This article is part of a supplement entitled Building Thriving Communities Through Comprehensive Community Health Initiatives, which is sponsored by Kaiser Permanente, Community Health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…The two prior ECE plate waste studies presenting milk and beverage data likely also found increased milk waste, though the finding was not directly reported. Both reported no significant changes in consumption despite increased dairy serving [ 18 ] and compliance with milk guidelines [ 17 ]. Over time, as children adjust their taste preferences for low and nonfat milk, it is possible that consumption may increase and waste decrease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two prior ECE plate waste studies presenting milk and beverage data likely also found increased milk waste, though the finding was not directly reported. Both reported no significant changes in consumption despite increased dairy serving [ 18 ] and compliance with milk guidelines [ 17 ]. Over time, as children adjust their taste preferences for low and nonfat milk, it is possible that consumption may increase and waste decrease.…”
Section: Discussionmentioning
confidence: 99%
“…(The study reported consumption, but the measurement involved plate waste.) Woodward-Lopez et al (2018) examined shifts in consumption following family child care participation in a multi-sector community-wide obesity prevention initiative in Northern California [ 17 ]. The providers received training and they individually selected practices to adopt, including changes to feeding, mealtime environment, and parent engagement.…”
Section: Introductionmentioning
confidence: 99%
“…Although studies may have examined interventions to improve family day care environments, not having a parallel control group resulted in their exclusion. Online Appendix B provides an overview of such types of previous interventions undertaken in this setting (29)(30)(31)(32)(33)(34)(35)(36) .…”
Section: Study Selectionmentioning
confidence: 99%
“…In the US, approximately 60% of preschool aged children receive external, non-parental care [16,17]. Of these, 24% are cared for by a non-relative in a family child care home (FCCH) [18].…”
Section: Introductionmentioning
confidence: 99%